Sustained, Effective School-wide Lesson Study: How Do We Get There? (Journal of Contemporary Educational Policies and Practices, 2022)
Lesson Study, a form of collaborative, practice-based professional learning that originated in Japan, consists of cycles of experimentation and reflection on classroom instruction. This research examines three schools in the United States that have built and sustained effective School-wide Lesson Study, as indicated by: (1) Lesson Study participation by most or all teachers two years after the end of outside Lesson Study funding; and (2) evidence of impact on teaching and learning. Data from the two schools that use mathematics standardized tests designed to measure deep conceptual learning (but not the third school, where tests focus on procedural mastery) indicate substantial increases in mathematics achievement. All three schools serve mainly students from historically underserved populations, including students of color, English-language learners, and students from low-income families. Analysis of artifacts and observational notes from the three schools suggests four factors shaping effective, sustained Lesson Study: (1) teacher agency;(2) access to a sound instructional vision that values student thinking and makes it visible; (3) teachers’ content study and access to content expertise; and (4) site-developed strategic management structures. The central role of teacher agency in sustainability is one implication of the study.
Keywords: Lesson study; mathematics teacher; teaching through problem-solving; professional learning; public lessons; school-wide